Microsurfacing – An Eco-Efficient Tool for Road Safety and Pavement Maintenance - Gujar, Rajesh S.; Chauhan, Krupesh A.; Dadhich, Gautam (International Journal of Sustainable Construction Engineering and Technology, 2013)
With the development of infrastructure, in rapidly developing modern era, frequent maintenance of existing infrastructure, especially roads is of prime importance.  Microsurfacing is a preventive maintenance technique (preventative maintenance strategy aims at producing the most cost-effective improvements in pavement quality and life) involving three to six millimeter sized bitumen aggregate treated with a special emulsion.  The layer is neatly laid down on road section requiring maintenance.  This paper aims at focusing on the contributions made by researchers on Microsurfacing as a tool for pavement maintenance and repair.  Although the technique is finding its place in Indian sub-continents little late, but nevertheless it is universally considered as an inevitable tool as far as preventive pavement maintenance is concerned and should be used to extend life of the underlying pavement